Analysis of Occupational Safety Risks in Construction Projects: A Case Research of the Implementation of JSA and Hierarchy of Control - Adilla, Ade; Andre, Pancha; Nofta, Eriksa; Indah, Aryati (Devotion : Journal of Research and Community Service, 2025)
Occupational safety and health (K3 - Keselamatan dan Kesehatan Kerja)) is an important element that should not be ignored in the implementation of construction projects. This is due to the high level of risk in the construction industry, which is influenced by a dynamic work environment full of various activities. This research aims to evaluate the potential occupational safety hazards in construction projects using a specific approach. JSA serves as a systematic method for identifying hazards at each work stage, while Hierarchy of Control provides a structured framework for determining risk mitigation priorities based on control effectiveness levels, starting from elimination, substitution, engineering controls, administrative controls, to personal protective equipment (PPE). The research methodology uses a quantitative descriptive approach with the help of questionnaire instruments and field data. Data were analyzed using descriptive analysis, validity and reliability tests, correlation, and regression. The results of the research show that occupational safety risks in projects are relatively high, with several potential main hazards such as falling from height, being hit by materials, and contact with high temperatures. Of the 43 risk variables analyzed, 12 risks (27.91%) were included in the high-risk category and 25 risks (58.14%) were in the moderate-risk category. control is carried out through PPE and engineering control. The implementation of JSA and Hierarchy of Control has proven to be effective in identifying and lowering work risks. The conclusion of this research can be the basis for improving the K3 management system in a more measurable and sustainable direction.